Comparison of Ma-Griffith combined with a minimally invasive small incision to a modified suture technique for the treatment of acute achilles tendon ruptures - Li Jun; Yu Hao; Zhan Junfeng; Zhang Jisen; Xu Xinzhong; Yao Yunfeng; Tian Dasheng; Xie Jia (BMC Musculoskeletal Disorders, 2022)
Abstract Background The Achilles tendon is the strongest tendon in the human body, although it is also prone to injury and rupture. Currently, the best treatment method for acute Achilles tendon rupture remains controversial. The aim of this study was to compare the efficacy of the Ma-Griffith method combined with a minimally invasive small incision (M-G/MISI) with the modified suture technique (MST). Methods We conducted a retrospective review of the medical records of all patients who underwent treatment for acute Achilles tendon rupture between January 2012 and January 2020 at our hospital. Demographic characteristics, operative details, and postoperative complications were recorded, and data were statistically analyzed to compare the treatment efficacy of the two operative methods. Results A total of 67 patients were enrolled in the study, 34 of whom underwent M-G/MISI treatment, and 33 of whom underwent MST treatment. The intraoperative blood loss in the M-G/MISI group (16.47 ± 13.23 ml) was significantly lower than that in the MST group (34.55 ± 13.01 ml), and the difference was statistically significant (P ˂0.001). The incision in the M-G/MISI group (3.79 ± 1.81 cm) was significantly shorter than that in the MST group (5.79 ± 1.00 cm), and the difference was statistically significant (P˂0.001). The Achilles tendon rupture score and the American Orthopedic Foot and Ankle Society (AOFAS) score were higher than those of the MST group at the sixth month after the operation (P˂0.001). Postoperatively, there was 1 case of traumatic Achilles tendon rupture in the M-G/MISI group and 1 case each of infection and deep vein thrombosis in the modified suture group. Conclusions Compared with the MST group, the M-G/MISI group had better Achilles tendon and ankle function scores at 6 months postoperatively, and less bleeding and shorter incisions. M-G/MISI is less invasive than MST.